Pengelolaan Pendidikan Karakter di Pondok Pesantren Muhammadiyah "Miftakhul 'Ulum" Pekajangan Pekalongan - Aulia, Muhammad Fakhrial, Prof. Dr. Sutama, M. Pd, Dr. Tjipto Subadi, M. Si (2015)
This research is aimed to describe character education management indoor and outdoor at "Miftakhul 'Ulum" Muhammadiyah boarding school of Pekajangan Pekalongan. This research metodology is ethnography qualitative research, the process is more important than the result. Research subject, teaching learning process, goes in natural setting and there is no researcher's special treatment to control. Research conclusion shows that character education management indoor and outdoor has 3 (three) steps: planning included RPP making and target planning, actuating included doing RPP and exercise, and evaluating with test and non-test. Obstacles in character education management: less commitment teachers, indiscipline students, and the limited facilities and infrastructure.